The performance of photovoltaic (PV) systems : modelling, measurement and assessment - Pearsall, Nicola (Woodhead Publishing in energy, 2017)
"Photovoltaic (PV) systems provide electricity for a wide range of applications, with low environmental impact and utilizing our largest renewable energy source, the sun. In recent years, the installed capacity of PV systems around the world has grown rapidly. The technical and economic viability of any PV system is determined by the energy output of the system over its lifetime. 'The Performance of Photovoltaic (PV) Systems: Modelling, Measurement and Assessment' considers prediction, measurement and analysis of the performance of PV systems, so as to allow the reader to obtain a thorough understanding of the performance issues and the progress that has been made in optimising system performance. Following an essential introduction to the area, Parts 1 and 2 review the performance of the PV module and system respectively. Part 3 discusses the factors influencing the performance of PV systems in key application sectors"--Print version, page 4 of cover